SOME OBSERVATIONS ON THE LARVAL GROWTH OF THE COMMERCIALLY IMPORTANT PENAEID PRAWNS OF SOUTHWEST COAST OF INDIA - Rao, P Vedavyasa (Indian Journal of Fisheries, 2011)
Some aspects of larval growth of the commercially important penaeid prawns, Parapenaeopsis stylifera, Metapenaeus monoceros, M. dobsoni and Penaeus indicus are studied. Growth factor in different larval stages is almost constant for each species and is less than 2, except in protozoea I of P. stylifera and M. dobsoni. During transformation of the last nauplius to protozoea I maximum values of growth factor and percentage increase in length are noticed. In other stages the growth percentage varies from 4.47 to 76.96 in P. stylifera, 4.25 to 25.27 in M. monoceros, 3.S7 to 51.’il in M. dobsoni and 12.34 to 24.43 in P. indicus.